Signalling pathways controlling glycosaminoglycan (GAG) chain synthesizing enzyme gene expression as potential therapeutic target for atherosclerosis - Rostam, Muhamad Ashraf (2014)
Heart disease is the leading cause of death in Australia. Atherosclerosis is the major the underlying cause of most heart disease. It is a pathological condition where accumulation of LDL cholesterol and inflammatory products in the blood vessel wall leads to formation of atherosclerotic plaques. Treatments to reduce atherosclerosis have mainly focused on reducing established risk factors like high cholesterol level. However, the efficacy of such treatments is limited to around 30 percent. New targets directed at the blood vessel wall are important areas that are being investigated. This includes focusing on the role of extracellular matrix components like proteoglycans that trap LDL. TGF-β is a growth factor associated with atherosclerosis. In vascular smooth muscle cells, TGF-β induces increased elongation of the sugar chain known as glycosaminoglycan (GAG) on proteoglycans and hence increases its size. This leads to increased binding to LDL in the initial stage of atherosclerosis. Our hypothesis is that the increase in elongation of GAG chain is regulated by the TGF-β mediated increase in expression of enzymes that synthesize this chain. However, the specific enzymes and the precise signalling pathways that lead to this up-regulation are not known. Therefore, we aim to describe the TGF-β signalling pathway and the intermediary protein kinases and Smad transcription factors that lead to GAG gene expression. This study uses pharmacological as well as molecular approaches to understand the critical kinases and protein components that are involved. The outcome of this study is important because the key elements we identify will provide new information about the signalling pathways regulating modification of proteoglycan synthesis. This will facilitate the identification of therapeutic targets in prevention of atherosclerosis.